Influencing people honestly : ethical persuasion strategies for leaders, managers, and entrepreneurs (O'Reilly Media, 2016)
"The word "influence" rightfully smacks of manipulation. But what if you could influence others using communication strategies that were ethical and open? What if the strategies you used were so focused and fair that the very people you were trying to influence wanted you to use them? Those are the concepts you'll explore in this video, and you'll learn how to influence others through considerate, principled means."--Resource description page.